Obesity and pelvic floor dysfunction. Issue 4 (May 2015) - Ramalingam, Kalaivani; Monga, Ash
Abstract : Obesity is associated with a high prevalence of pelvic floor disorders. Patients with obesity present with a range of urinary, bowel and sexual dysfunction problems as well as uterovaginal prolapse. Urinary incontinence, faecal incontinence and sexual dysfunction are more prevalent in patients with obesity. Uterovaginal prolapse is also more common than in the non-obese population. Weight loss by surgical and non-surgical methods plays a major role in the improvement of these symptoms in such patients. The treatment of symptoms leads to an improvement in their quality of life. However, surgical treatment of these symptoms may be accompanied by an increased risk of complications in obese patients. A better understanding of the mechanism of obesity-associated pelvic floor dysfunction is essential. Highlights: Global pelvic floor dysfunction is associated with obesity. Weight loss improves urinary symptoms. Sexual dysfunction improves after weight loss. Prolapse symptoms do not improve after weight loss.